IMPLEMENTASI MODEL PEMBELAJARAN BLENDED LEARNING TIPE FLIPPED CLASSROOM UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Wulandari, Yessi; Halim, Abdul; Nasrullah, Nasrullah; Syukri, Muhammad; Elisa, Elisa (Tatar Pasundan: Jurnal Diklat Keagamaan, 2023)
The goal of this research was to find out if students were more enthusiastic about learning about mechanical wave material using the flipped-classroom paradigm of blended learning. The methodology of this investigation is quantitative. This study used a quasi-experimental strategy based on a pre- and post-test control group design. This study was carried out at SMA Negeri 1 Bireuen. Students from SMA Negeri 1 Bireuen's IPA class of the 2021–2022 school year made up the study's population. This research employed a "purposive sampling" technique. Thirty students from IPA XI class B served as the study's experimental group, while the same number from IPA XI class C was control group. The researchers used a student interest survey that asked about four factors: pleasure, attention, interest, and involvement. Percentage interest surveys administered both before and after implementing the flipped-classroom into both experimental class and controlled class. Research and data analysis have led to the conclusion that students who adopt a blended learning model of the flipped-classroom variety show a marked improvement in their learning interest when compared to students who adopt conventional model of instruction (direct interaction).Keywords: Interest; Flipped Classroom; Blended Learning